THE RELATION BETWEEN THE AUDITOR OF THE FEDERAL FINANCIAL SUPERVISION BUREAU AND THE INTERNAL AUDITOR: A FIELD STUDY IN THE BANKS OF THE IRAQI GOVERNMENT (World Economics and Finance Bulletin, 2022)
The study aims at clarifying the relationship between the Federal Auditor of the Financial Supervision Bureau and the internal auditor in the Iraqi banks. This will be done through creating and developing a questionnaire to collect data from the community of the study (the auditors of the financial supervisory Bureau and the internal auditors of the Iraqi banks). In one hand, 55 copies are distributed on the auditors of the Bureau and 48 copies are returned back for statistical analysis. In the other hand, 60 copies are distributed on the internal auditors of the Iraqi banks and 50 copies are returned back for the statistical analysis. The total of the samples is 98 auditors are selected depending on random method, where the packages of statistical analysis (SPSS) are used in analyzing the data. This study comes up with some results, including: audit committee plays its role in strengthening the relationship between the auditors of the Federal Financial supervision Bureau and the internal auditors in the Iraqi banks, as is seen by the data of the study. The committee has the responsibility of executing the observations and recommendations provided by the system of internal control in the banks, that the Bureau’s auditor uses the reports and worksheets of the internal auditor to obtain a full understanding of the control system as well as evaluating the effectiveness and efficiency of the internal control system. The study recommended that a committee must ensure holding periodical meetings with the auditors of the Bureau and the internal auditors, attended by the internal auditors to exchange ideas, discuss plans and developments and solve problems. The auditor of the Bureau should take into consideration the work accomplished by the internal auditor, to repeating work and wasting time. The auditor must also depend on the reports of the internal auditor in his audit of the branches and departments affiliated with the bank.